A new fault-ride-through strategy for MTDC networks incorporating wind farms and modular multi-level converters. (November 2017) - Tzelepis, D.; Rousis, A. Oulis; Dyśko, A.; Booth, C.; Strbac, G.
Highlights: Large-scale PMSG, FRC based wind farms under faulty operating conditions considered. High voltage direct current links with modular multi-level converters investigated. A novel DC voltage control strategy for improved FRT performance proposed. Simulation studies of the wind farms operation for various onshore grid faults. The simulated DC voltage controller response experimentally validated. Abstract: This paper presents a DC voltage control strategy for enhancing the fault-ride-through (FRT) capability of wind farms comprising of fully rated converter permanent magnet synchronous generators (FRC-PMSGs) connected to multi-terminal high voltage direct current (MT-HVDC) grids through modular multi-level converters (MMCs). The proposed FRT strategy is implemented on a master controller located in the offshore AC substation of each wind farm. The underlying issue addressed via the scheme relates to over-voltages in the HVDC links when the power transfer is disrupted due to faults occurring in the AC onshore grid. The corresponding Matlab/Simulink® model has been validated using transient simulation, while the practical feasibility of the controller is demonstrated utilising Opal-RT © real-time hardware platform.